Sarcolemmal membrane associated proteins: Structure-function analyses and localization studies - Guzzo, Rosa M (University of Ottawa (Canada), 2003)
Previous work from our lab identified a novel cDNA encoding a family of tail-anchored coiled-coil integral membrane proteins termed SLMAPs (sarcolemmal membrane associated proteins) (Wigle et al., 1997). Subsequent studies determined that SLMAPs are encoded by a single gene, and alternative splicing yields three SLMAP isoforms, including two muscle-specific variants (SLMAP1, SLMAP2) and a ubiquitously expressed isoform (SLMAP3). Here, I report a series of studies designed to examine putative novel and isoform specific functions of SLMAPs in striated muscle and fibroblast cells. The tissue distribution and subcellular localizations of SLMAPs were examined in developing and adult mouse tissues in order to correlate SLMAP expression with specific physiological or developmental process(es). Immunohistochemical staining using polyclonal anti-SLMAP antibodies revealed that SLMAPs are highly expressed in developing somites and cardiac tissue. Confocal microscopy determined that SLMAPs localized within the discrete membrane structures (sarcoplasmic reticulum and T-tubules) of developing and mature skeletal and cardiac muscle, respectively. These localization studies suggest a correlative role for SLMAPs in excitation-contraction (EC) coupling mechanisms. In vivo expression of SLMAPs in pre-fusion myoblasts indicated a possible involvement in skeletal myogenesis. An additional SLMAP protein was expressed under conditions that promote differentiation in cultured myoblasts. Deregulation of SLMAPs by ectopic expression in myoblasts resulted in a potent inhibition of fusion without affecting the expression of muscle-specific genes. Protein-protein interaction assays demonstrated that the leucine zipper motifs in SLMAPs mediate SLMAP homodimer formation. Proteomic analysis further revealed that a muscle-specific SLMAP variant binds a component of the contractile apparatus (cardiac myosin heavy chain). The expression of a cardiac-specific SLMAP isoform that resides in distinct membranes, self assembles and interacts with the contractile apparatus further suggest a unique role for this molecule in excitation-contraction coupling mechanisms. Alternative splicing mechanisms generate SLMAP variants with divergent carboxyl-terminal hydrophobic segments, which target SLMAPs to different membrane compartments. Immunocytochemistry studies revealed that the expression of the first transmembrane domain directs a 6Myc-SLMAP fusion protein to the endoplasmic reticulum in COS7 cells. (Abstract shortened by UMI.)
Keywords: Biology, Cell.; Chemistry, Biochemistry.